PENGARUH KEAJAIBAN QUIZIZZ YANG MELEJITKAN SEMANGAT SISWA SEKOLAH DASAR: SEBUAH KISAH FANTASTIS YANG MENERBANGKAN HASIL BELAJAR KE ANGKASA - Risaad, Rismayani; Sarwi Mahmud; Tri Joko Raharjo; Decky Avrilianda; Bambang Subali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
How the use of the Quizizz application affects students' learning abilities in elementary schools is the subject of this research. Quizizz is one of the web-based learning tools expected to solve that problem can help teachers and students improve their own competence, increase students' ability and desire to learn using conventional learning media. This research uses various systematic literature review (SLR) research methods, namely, identifying, reviewing, evaluating and interpreting all research that has been conducted on this subject. To search for data, Google Scholar was used with relevant keywords. To collect data, each article collected is recorded in this literature research article. These articles are then analyzed and tabulated in a table containing the researcher's name, year of publication, journal name, and research results. According to 28 researched articles, the Quizizz App helps elementary school students learn better. The Quizizz application is considered interesting, interactive and effective for evaluating learning because it can increase student motivation, understanding of concepts, mastery of material and academic performance. The results of this research show how much influence Quizizz has on the ability of elementary school students who focus on knowing how Quizizz impact on the learning outcomes of elementary school students, shows that many articles and journals have been published on how Applications Quizizz affects the academic achievement of elementary school students It can be said that the use of Quizizz has an impact on the academic achievement of elementary school students. Quizizz proven to increase student motivation, their ability to understand concepts, mastery of material, and their overall academic performance. Quizizz It is considered interesting, interactive and effective as a medium for evaluating learning in elementary schools because it has attractive visual features and designs.